THE DIFFERENCE BETWEEN BRITISH AND AMERICAN ENGLISH SPELLING, VOCABULARY, AND PRONUNCIATION.docx (Лучшие интеллектуальные исследования, 2025)
Abstract :This paper explores the differences between British and American English, focusing on key areas such as spelling, vocabulary, and pronunciation. The comparison of these two major dialects of the English language offers insight into how language evolves across different regions and cultures. The study also highlights how these differences can affect communication, learning, and cultural identity. This paper aims to provide a comprehensive understanding of the distinctions between British and American English.